2010
DOI: 10.1016/j.ultsonch.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound in grape mash treatment in juice processing

Abstract: Recently, application of ultrasound has attracted considerable interest as an alternative approach to traditional methods. In this study, response surface methodology (RSM) was used to optimize the conditions for grape mash treatment by ultrasound and by combination of ultrasound and enzyme. The results indicated that optimal conditions were the temperature of 74 degrees C and the time of 13 min for sonication treatment; and were the enzyme concentration of 0.05% and the time of 10 min for combined ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
53
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 36 publications
13
53
1
1
Order By: Relevance
“…These results agreed with previous researches, which reported that ultrasound promotes high extractability for sugars (Fernandes et al, 2009;Lieu & Le, 2010). Due to the cell disruption, US treatment has been applied in extraction protocols (Eh & Teoh, 2012;Paniwnyk, Cai, Albu, Mason, & Cole, 2009;Rodrigues, Pinto, & Fernandes, 2008).…”
Section: Sugar Concentrationsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agreed with previous researches, which reported that ultrasound promotes high extractability for sugars (Fernandes et al, 2009;Lieu & Le, 2010). Due to the cell disruption, US treatment has been applied in extraction protocols (Eh & Teoh, 2012;Paniwnyk, Cai, Albu, Mason, & Cole, 2009;Rodrigues, Pinto, & Fernandes, 2008).…”
Section: Sugar Concentrationsupporting
confidence: 92%
“…Rawson et al (2010) also observed a decrease in the phenolic content of sonicated watermelon juice when the temperature was increased from 25 to 45°C, with the temperature effect more pronounced at higher processing times (10 min). On the other hand, Lieu and Le (2010) evaluated the application of ultrasound treatment in grape juice and found that the sonicated samples had an increase of 114.3% in the concentration of total phenolics, making evident that the effect of sonic waves in foods depends on the food matrix besides processing conditions.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…With the advance of storage (>14 days) the untreated sample had an increase of these compounds, while thermoultrasonicated and pasteurized juices presented slight variability. On day 1, similar results has also been reported by Lieu et al [60] for grape, Sathirasegaram et al [54] for mango and Bhat et al [5] for lime juice, which presented higher total phenolic content after sonication. Phenolic compounds are found in soluble form in the vacuole or bound to the pectin, cellulose, hemicellulose, and lignin traces of the cell wall [61].…”
Section: Microbiological Analysissupporting
confidence: 87%
“…While a slight decrease in the viscosity of Sohiong juice was observed as the ultrasound treated pulp was subjected to higher incubation times (Table ). The ultrasound assisted enzymatic treatment breaks down the cohesive network of pectinaceous substances thus decreasing the water holding capacity of the pulp (Lieu & Le, ). Therefore, dissolved solids and available water present in the pulp was released easily to the juice to increasing the juice yield (Saxena et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It also enhances the shelf life and microbial safety of fruit juices (Tiwari, O'Donnell, Muthukumarappan, & Cullen, ). Various researchers have used ultrasound in different food applications for extraction (Bora, Handique, & Sit, ; Ertugay & Başlar, ; Lieu & Le, ; Nithila et al, ). This can also be used for extraction of juice from Sohiong fruit.…”
Section: Introductionmentioning
confidence: 99%